Safe in the City - Improving Perceived Safety in Public Spaces - KAARTINEN, JOHANNA; WICKERSTRÖM, CHRISTIAN (My University, 2018)
To feel safe is an inherent need within every human being. In the era of rapid urbanization, the topic of safety becomes very actual and should be addressed in various contexts, including design research. To find out how Interaction Design can contribute to the development of safer future cities, this master thesis explored the factors affecting perceived safety in the city of Gothenburg. Also, it investigated what role a smartphone application can have in increasing perceived safety. The research process followed Research Through Design approach within the Double Diamond framework. The nature of the process was iterative and reflective. Additionally, a literature study, survey, and three Google Design Sprints were conducted. The research findings regarding perceived safety were divided into three categories; personal, social and physical factors. To be able to emphasize the most critical aspects of these factors, expert interviews and observation were performed. The study resulted in empirically and theoretically grounded guidelines. They are aimed to support interaction designers in their work when designing a solution that enhances perceived safety in public places. The guidelines are supported by a conceptual model of perceived safety that visualizes the dynamic relationships between the different factors. Additionally, a lo-fi prototype of a smartphone application “Walk with Me” that aims to improve perceived safety through social connections was created and validated through user testing. The findings from the user testing resulted in design implications. The outcome of this thesis aims to contribute to further research within the field of Interaction Design regarding perceived safety in public spaces.
Keywords: Data- och informationsvetenskap; Computer and Information Science